2022
DOI: 10.2196/29539
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Infection and Symptoms Among Emergency Medicine Residents and Fellows in an Urban Academic Hospital Setting: Cross-sectional Questionnaire Study

Abstract: Background COVID-19, an illness caused by the novel coronavirus SARS-CoV-2, affected many aspects of health care worldwide in 2020. From March to May 2020, New York City experienced a large surge of cases. Objective The aim of this study is to characterize the prevalence of illness and symptoms experienced by residents and fellows in 2 New York City hospitals during the period of March to May 2020. Methods A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Infection rates among trainees also likely varied across regions, with some trainees unable to prepare for or take the exam. 34 Interpretation of SITE scores as an indicator of program performance is difficult given it is a one-day test and as such may include bias due to non-random missingness. Despite increases in the number of applicants to pediatric subspecialties during the pandemic, 35 many programs did not require their fellows to take SITE in 2021 and 2022, with refunds being offered by ABP.…”
Section: Discussionmentioning
confidence: 99%
“…Infection rates among trainees also likely varied across regions, with some trainees unable to prepare for or take the exam. 34 Interpretation of SITE scores as an indicator of program performance is difficult given it is a one-day test and as such may include bias due to non-random missingness. Despite increases in the number of applicants to pediatric subspecialties during the pandemic, 35 many programs did not require their fellows to take SITE in 2021 and 2022, with refunds being offered by ABP.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study to investigate this question specifically amongst EDPs providing care to COVID-19 infected individuals post vaccination roll-outs. Early in the COVID-19 pandemic, there were several studies that evaluated for the presence of SAR-CoV-2 antibodies in HCWs, reporting a prevalence ranging from 5 to 42% [ [1] , [2] , [3] , 10 ]. Important to note that this was a time many institutions lacked appropriate PPE.…”
Section: Discussionmentioning
confidence: 99%
“…Emergency department providers (EDPs) including physicians, residents, and Advanced Practice Providers (APPs) have experienced some of the highest exposure rates with individuals infected with the SARS-CoV-2 virus. Studies following the initial wave of infections suggested confirmed positive rates in physicians and APPs ranging from 5 to 40% [ 1 , 2 ]. Following the availability of COVID-19 vaccines in December of 2020, the incidence of infection in health care workers (HCWs) had significantly decreased.…”
Section: Introductionmentioning
confidence: 99%
“…Proper usage of these terminologies is mandatory and should be corrected throughout the manuscript. The authors [1] have done a fine job in addressing their shortcomings and my previous comments. I only have a few more minor comments that need to be addressed:…”
Section: Why Wasn't Multiple Regression or Linear Regression Analysis Performed?mentioning
confidence: 99%